Study on the seismic performance of rural houses masonry walls with different geometries of open-hole area reduction. (July 2022) - Li, Mingyang; Zhu, Eryu; Wang, Bin; Zhu, Chunqi; Liu, Lei; Yang, Wei
Abstract: Masonry houses account for 90% of all rural houses in China, which is of great practical significance for studying the seismic strengthening of masonry houses. Based on the actual structural forms of existing farm houses in Beijing, this paper proposes a cost-effective reinforcement scheme using additional masonry walls with different geometries to strengthen the open-hole brick walls to fulfill the seismic protection requirements. The open-hole masonry walls were examined and compared in load–displacement, hysteresis curve, skeleton curve, ductility, energy consumption, and stiffness degradation through quasi-static tests and finite element analysis. The test results were verified by finite element analysis. In addition, the reinforcement effect was verified regarding damage characteristics, hysteresis curves and skeleton curve trends. Compared to the unreinforced wall, the wall reinforced by adding 740 mm to one side of the open brick window increased the ultimate bearing capacity by 136% and the damage displacement by 56%. By adding 370 mm to one side of the open-hole brick masonry window, the ultimate bearing capacity increased by 83%, and the damage displacement increased by 10%. Furthermore, by adding 370 mm of wall symmetrically along both sides of the open-hole brick masonry window, the ultimate bearing capacity increased by 185% and the damage displacement increased by 67%. These results indicate that the reinforcement technique can effectively improve the lateral stiffness and seismic performance of the open-hole masonry walls. In addition, the formula for calculating the seismic bearing capacity of open-hole walls reinforced with masonry walls is also proposed.